Upaya Meningkatkan Kemampuan Menulis Puisi Menggunakan Teknik Akrostik Pada Siswa Kelas XI.10 SMA Negeri 5 Palembang - Sari, Mira; Oktriyanti, Selvia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Based on the observation in class XI.10 SMA Negeri 5 Palembang, it is known that students' ability in writing poetry is not optimal. Students tend to choose inappropriate diction, with these constraints, teachers must be able to choose the right technique for learning to write poetry. One of the appropriate techniques is the acrostic technique, therefore, the subject of this research is to examine the ability of students to write poetry in class XI.10 SMA Negeri 5 Palembang through the application of the acrostic technique. This study aims to see the extent of students' ability in writing poetry using the acrostic method. This study used a class action research design through descriptive analysis. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this study were 31 students of class XI.10 SMA Negeri 5 Palembang with 15 male and 16 female students. The data collection techniques used were observation, and tests. The overall data obtained was analyzed through stages: data reduction, data presentation, and conclusions. Based on the research results obtained, it can be concluded that the pre-action results in writing poetry are still relatively poor. After the action was taken with the application of the acrostic method in improving the learning of writing poetry, it showed a moderate to excellent improvement. The final result of this study shows that the application of acrostic technique in learning to write poetry can improve students' potential in poetry writing skills.